Analisis Hasil Penerapan Apk Quiziz Pada Pembelajaran Bahasa Inggris Sebagai Bahan Evaluasi siswa kelas XI MIPA 1 Di SMA 6 Maros - Ririn Asta Rina; Nur Indah Sari B; Salma Hera; Akram Akram (Sintaksis : Publikasi Para ahli Bahasa dan Sastra Inggris, 2024)
This study aims to analyze the results of the application of the Quiziz application in English language learning as evaluation material for grade XI Mipa 1 students at SMA 6 Maros. The research method used is descriptive research with a quantitative approach. The sample of this study was class XI Mipa 1 students consisting of 17 people. Research data was collected through the use of the Quiziz application which is used as an evaluation tool in English language learning. The collected data is analyzed using descriptive statistical methods to analyze the level of student understanding of the material taught. The results showed that the application of the Quiziz application in English language learning made a significant contribution in improving student understanding. Students show improvement in evaluation scores after using the Quiziz app as evaluation material. In addition, students also provide positive feedback regarding the use of this application in English language learning. This study provides recommendations for English teachers to consider using the Quiziz application as an evaluation tool in learning. In addition, this research can also be a reference for schools or other educational institutions in choosing and implementing the right application to improve English learning outcomes.